2010
DOI: 10.1051/vetres/2010025
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of neutrophils but not mammary alveolar macrophages in a murine model of acuteEscherichia colimastitis

Abstract: Mastitis, the inflammation of the mammary gland, is an important disease affecting dairy animals worldwide. The disease is caused by mammary pathogenic bacteria and Escherichia coli are frequently implicated. Virulence factors of mammary pathogenic E. coli are only partially known and intramammary challenge with LPS elicits neutrophil recruitment in experimental bovine and murine mastitis models. We have previously shown that neutrophil recruitment in LPS-induced murine mastitis is strictly dependent on mammar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 22 publications
5
33
0
2
Order By: Relevance
“…4). This observation corroborates the important role of neutrophils early in the course of infection, as reported for E. coli mastitis in the cow (48) and the mouse mastitis model (18). Our data suggest that IL-17A contributed to bacterial containment and neutrophil recruitment only after the initial 24-h period.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…4). This observation corroborates the important role of neutrophils early in the course of infection, as reported for E. coli mastitis in the cow (48) and the mouse mastitis model (18). Our data suggest that IL-17A contributed to bacterial containment and neutrophil recruitment only after the initial 24-h period.…”
Section: Discussionsupporting
confidence: 91%
“…2), and the depletion experiment confirmed that neutrophils are important for the control of infection in our model (Fig. 4), as previously shown by others (18). The early influx of neutrophils was paralleled by an early increase in MIP-2a, a chemokine that attracts neutrophils.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This inflammation response pointing out to additional factors beyond LPS and additional cells beyond alveolar macrophages play a role in the inflammatory response to E. coli. It has been suggested that in the absence of functional TLR4 the infecting E. coli P4 invaded epithelial cells with high efficiency, forming intracellular microcolonies, since invasion of epithelial cells by E. coli is limited by alveolar macrophages using a process dependent on TLR4 signaling (Gonen et al, 2007;Elazar et al, 2010b;Schukken et al, 2011).…”
Section: The Importance Of These Cells Is Demonstrated By Theirmentioning
confidence: 99%
“…Atribui-se aos leucócitos polimorfonucleares (PMNL) a maior responsabilidade na proteção da glândula mamária aos patógenos invasores (Paape et al 2003, Elazar et al 2010. Entretanto, deve-se considerar a delicada inter-relação que rege os mecanismos imunes, e o papel crucial dos macrófagos na detecção e montagem da resposta imune, e consequentemente nos mecanismos de defesa da glândula mamária (Della Libera et al 2006).…”
Section: Introductionunclassified